Application of the Consumer Protection Law in Electronic Transactions - Wibowo, Heri; Sebyar, Muhamad Hasan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the implementation of consumer protection laws in e-commerce transactions in Indonesia. The method used in this research is a normative legal research method with a statutory approach. The data collection technique is literature study. The data in this research uses primary and secondary data. The research results show that the implementation of the law in this Law is carried out through several steps, including (1) enforcing special regulations created to regulate consumer rights and obligations in relation to electronic transactions, (2) the government taking firm action against violations of consumer rights in electronic transactions involving law enforcement officials. (3) increase consumer awareness. Various initiatives educate and inform consumers about their rights and potential risks and how they can protect themselves when making online transactions.